Pengembangan Model Pembelajaran Contextual Teaching and Learning untuk Meningkatkan Kreativitas Siswa - Siti Fatmawati (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2018)
The learning model is one of the requirements in improving student learning, not only in matters relating to student interest in class, but also in student creativity in following the learning process. One of the learning models that is currently trending is contextual teaching and learning. This research discusses how the development of a contextual teaching and learning model in MIS Tarbiyatul Mubtadiin Labruk Lor Lumajang is, so that it can increase student creativity. This research is a field study using a qualitative descriptive approach. The result showed that the development of a learning model for contextual teaching and learning was carried out in several ways; development through constructivism, development through questioning and learning Community.